Modeling excitonic line shapes in weakly disordered semiconductor nanostructures - Kuznetsova, I.; Gőgh, N.; Förstner, Jens; Meier, Torsten; Cundiff, S. T.; Varga, I.; Thomas, P. (Physical Review B)
Excitonic spectra of weakly disordered semiconductor heterostructures are simulated on the basis of a one-dimensional tight-binding model. The influence of the length scale of weak disorder in quantum wells on the redshift of the excitonic peak and its linewidth is studied. By calculating two-dimensional Fouriertransform spectra we are able to determine the contribution of disorder to inhomogeneous and also to homogeneous broadenings separately. This disorder-induced dephasing is related to a Fano-type coupling and leads to contributions to the homogeneous linewidth that depends on energy within the inhomogeneously broadened line. The model includes heavy- and light-hole excitons and yields smaller inhomogeneous broadening for the light-hole exciton if compared to the heavy-hole exciton, which agrees qualitatively with the experiment.
Keywords: tet_topic_qw

Microscopic analysis of charge and spin photocurrents injected by circularly polarized one-color laser pulses in GaAs quantum wells - Duc, Huynh Thanh; Förstner, Jens; Meier, Torsten (Physical Review B)
The dynamics of charge and spin injection currents excited by circularly polarized, one-color laser beams in semiconductor quantum wells is analyzed. Our microscopic approach is based on a 14x14 k · p band-structure theory in combination with multisubband semiconductor Bloch equations which allows a detailed analysis of the photogenerated carrier distributions and coherences in k space. Charge and spin injection currents are numerically calculated for [110]- and [001]-grown GaAs quantum wells including dc population contributions and ac contributions that arise from intersubband coherences. The dependencies of the injection currents on the excitation conditions, in particular, the photon energy are computed and discussed.
Keywords: tet_topic_qw

Ultranarrow coupling-induced transparency bands in hybrid plasmonic systems - Zentgraf, Thomas; Zhang, Shuang; Oulton, Rupert F.; Zhang, Xiang (Physical Review B)

Inversion-asymmetry-induced spin splitting observed in the quantum oscillatory magnetization of a two-dimensional electron system - Wilde, M. A.; Reuter, Dirk; Heyn, Ch.; Wieck, A. D.; Grundler, D. (Physical Review B)

Collective single-mode precession of electron spins in an ensemble of singly charged (In,Ga)As/GaAs quantum dots - Greilich, A.; Spatzek, S.; Yugova, I. A.; Akimov, I. A.; Yakovlev, D. R.; Efros, Al. L.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Inversion-asymmetry-induced spin splitting observed in the quantum oscillatory magnetization of a two-dimensional electron system - Wilde, M. A.; Reuter, Dirk; Heyn, Ch.; Wieck, A. D.; Grundler, D. (Physical Review B)

Conversion of bound excitons to free excitons by surface acoustic waves - Völk, S.; Wixforth, A.; Reuter, Dirk; Wieck, A. D.; Ebbecke, J. (Physical Review B)

Measurement of the Knight field and local nuclear dipole-dipole field in an InGaAs/GaAs quantum dot ensemble - Auer, T.; Oulton, R.; Bauschulte, A.; Yakovlev, D. R.; Bayer, M.; Verbin, S. Yu.; Cherbunin, R. V.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Carrier relaxation dynamics in self-assembled semiconductor quantum dots - Kurtze, H.; Seebeck, J.; Gartner, P.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M.; Jahnke, F. (Physical Review B)

Water adsorption on the α-Al2O3(0001) surface - Thissen, P.; Grundmeier, G.; Wippermann, S.; Schmidt, Wolf Gero (Physical Review B)

Rare-earth defect pairs in GaN: LDA+U calculations - Sanna, Simone; Schmidt, Wolf Gero; Frauenheim, Th.; Gerstmann, Uwe (Physical Review B)

Adsorption structure of cyclopentene on InP(001)(2×4) - Passmann, Regina; Favero, Priscila; Schmidt, Wolf Gero; Miotto, Ronei; Braun, Walter; Richter, Wolfgang; Kneissl, Michael; Esser, Norbert; Vogt, Patrick (Physical Review B)

First-principles calculations of clean Au(110) surfaces and chemisorption of atomic oxygen - Landmann, M.; Rauls, E.; Schmidt, Wolf Gero (Physical Review B)

Transition from thin-film to bulk properties of metamaterials - Rockstuhl, Carsten; Paul, Thomas; Lederer, Falk; Pertsch, Thomas; Zentgraf, Thomas; Meyrath, Todd P.; Giessen, Harald (Physical Review B)

Hysteretic magnetotransport inp-typeAlxGa1−xAsheterostructures with In/Zn/Au Ohmic contacts - Grbić, B.; Leturcq, R.; Ihn, T.; Ensslin, K.; Blatter, G.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Magnetic-barrier-induced conductance fluctuations in quantum wires - Hugger, S.; Xu, Hengyi; Tarasov, A.; Cerchez, M.; Heinzel, T.; Zozoulenko, I. V.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Temperature-induced spin-coherence dissipation in quantum dots - Hernandez, F. G. G.; Greilich, A.; Brito, F.; Wiemann, M.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Phonon-assisted tunneling between singlet states in two-electron quantum dot molecules - Grodecka, A.; Machnikowski, P.; Förstner, Jens (Physical Review B)
We study phonon-assisted electron tunneling in semiconductor quantum dot molecules. In particular, singletsinglet relaxation in a two-electron-doped structure is considered. The influence of Coulomb interaction is discussed via comparison with a single-electron system. We find that the relaxation rate reaches similar values in the two cases but the Coulomb interaction shifts the maximum rates toward larger separations between the dots. The difference in electron-phonon interaction between deformation potential and piezoelectric coupling is investigated. We show that the phonon-induced tunneling between two-electron singlet states is a fast process, taking place on the time scales of the order of a few tens of picoseconds.
Keywords: tet_topic_qd

Water adsorption on clean Ni(111) and p(2×2)-Ni(111)-O surfaces calculated from first principles - Wippermann, S.; Schmidt, Wolf Gero (Physical Review B)

Spatial modulation of molecular adsorption energies due to indirect interaction - Blankenburg, S.; Schmidt, Wolf Gero (Physical Review B)